PERLINDUNGAN HUKUM DAN PEMULIHAN BAGI ANAK DAN PEREMPUAN KORBAN KEKERASAN (STUDI KASUS DI PENGADILAN NEGERI BREBES) - Joni Minulyo; Koerniatmanto Soetoprawiro; Ratna Riyanti (Research Report - Humanities and Social Science, 2012)
Social change that will be studied here is on a problem of family violances. Many cases showed that children and women were the victim of family violances. The problem is that the Indonesian social culture sees the fenomena were privat or family internal problem.This research concluded that Indonesian positive law has tried to change this fenomenon. There are two undangs-undangs those change this fenomenon. They are:Undang-Undang Nomor 23 Tahun 2003 on Children ProtectionUndang-Undang Nomor 23 Tahun 2004 on Elimination to Violances in HouseholdsThe problem is in the implementation of those two undang-undangs.